Clinical presentation of tubal ectopic pregnancy - Garikapati, Kavitha; Devi, M. Parvathi; Goud, N. Alekya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: When the fertilized ovum gets implanted at site other than normal position of uterine cavity, it is known as ectopic pregnancy. Incidence of ectopic pregnancy is 1-2% of all reported pregnancies. It is an unmitigated disaster of human production and the most important cause of morbidity and mortality in first trimester with major cause of reduced child bearing potential. It is notorious in its clinical presentation, challenging the attending physician. Methods: women with risk factors, signs and symptoms and with confirmed diagnosis. Women discharged against medical advice. Study population is 50. Retrospective analysis for 3 years (2016-2019). Objectives of this study were to study the incidence, risk factors, clinical presentation, diagnosis and changing trends of modern management. Results analysed after entering the information in the excel sheets using descriptive analysis Results: Out of 4940 deliveries, 50 were tubal ectopic pregnancies 1.012%. Women aged 20-25 years were 52%. In our study, multiparous were 68%. Common symptoms were abdominal pain 80.2%, amenorrhea 72%, urine gravindex test positive 92.8%. Etiology was PID 20%, previous ectopic pregnancy 4%, IUCD 4%, LSCS with tubectomy 16%, most common site is ampulla 82%. About 78% were ruptured. Tubal abortions 4%, salpingectomy done in 82%. Laparotomy in 2.43% in hemodynamically unstable. Medical management 8%. Salpingostomy in 4% and expectant management 2%. Morbidity in the form of blood transfusion 23.48%, DIC with ICU admission 2%. No mortality. Conclusions: A high index of clinical suspicion with underlying risk factors may get us early diagnosis for timely intervention.